Anuran Of Taman Negara Johor Endau Rompin - Mohamed, Maryati; Awang, Muhammad Taufik; Tokiman, Lili; Hee, Kueh Boon (Penerbit UTHM, 2016)
This book tries to capture the beauty of anurans (frog and toads) in all aspects; morphology and ecology as well as to give the people new knowledge about anuran. This book is good for those who want to learn more about the anuran. The importance of the frogs and toads in Malaysia, particularly at Taman Negara Johor Endau-Rompin (TNJER) is manifold. Firstly, it is an indicator of the pristine characteristics of the tropical rain forest is with high humidity, and abundant water bodies. Temperature also indirectly affect the frog and toad diversity. Secondly, some frog species are used as food sources for local ethnic, which may become a problem to the conservation effort of the park management. Thirdly its potential to be established in raising awareness on biodiversity and educating people on diversity is worth its conservation. Elsewhere frog also be found to be useful as one of the product for the tourism. If anything close is to be continued in the park is that some species are endemic to this forest reserve. Conservation and preservation effort for the living things in this forest reserve especially the anuran has not been done, it will be extinct one day. Besides, the fact that some species are endemic to this forest reserve become the strong reason why it should be preserve.